Analisis Integrasi Nilai-Nilai Keislaman dalam Pembelajaran Matematika pada Kurikulum Merdeka di Smpn 210 Jakarta - Alliya Imani Zahra; Aniqo Aini Samsul Putri; Amirullah (Jurnal Inovasi Global, 2024)
One of the programs in the Independent Curriculum that attempts to mold students' character and improve their abilities in line with Pancasila values is the Strengthening Pancasila Student Profile (P5) Project. One way to address the issues with Indonesian education is through the P5 program. Up until now, the country has tended to emphasize students' cognitive (knowing) abilities more than their affective (attitudes) and psychomotor (skills) components. This study intends to describe the P5 Program's implementation and assess the Islamic educational ideals that are incorporated into the Merdeka Curriculum, with a focus on the P5 Program's application in mathematics at SMP Negeri 210 Jakarta. This study combines phenomenological research types with qualitative approaches. This study employed observation, documentation, and interviewing as data gathering methods. One of the programs in the Independent Curriculum that attempts to mold students' character and improve their abilities in line with Pancasila values is the Strengthening Pancasila Student Profile (P5) Project. One way to address the issues with Indonesian education is through the P5 program. Up until now, the country has tended to emphasize students' cognitive (knowing) abilities more than their affective (attitudes) and psychomotor (skills) components. This study intends to describe the P5 Program's implementation and assess the Islamic educational ideals that are incorporated into the Merdeka Curriculum, with a focus on the P5 Program's application in mathematics at SMP Negeri 210 Jakarta. This study combines phenomenological research types with qualitative approaches. This study employed observation, documentation, and interviewing as data gathering methods. The outcomes demonstrated how successfully the P5 Program in the Merdeka Curriculum has been implemented at SMP Negeri 210 Jakarta. The development of students' skills, abilities, and competences as well as their character formation in line with Pancasila values are signs of success. The P5 Program in the Merdeka Curriculum at SMP Negeri 210 Jakarta has been implemented in a methodical manner, beginning with planning, carrying out, and assessing the program. Activities of all kinds that are pertinent to the Islamic education values, including moral, social, and creedal values, are included in the program's implementation.